PENGARUH PELAKSANAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR IPS SISWA - andi fathur asdar (Universitas Negeri Makassar, 2016)
The objective of this research was to describe: 1) Teacher ability in the implementation of cooperative learning Think Pair Share, 2) Ttudent activities in the implementation of cooperative learning Think Pair Share, 3) Tearning result on IPS before and after the implementation of cooperative learning Think Pair Share, 4) learning result on IPS before and after learning process with lecture method, 5) to find out the influence of the implementation of cooperative learning Think Pair Share toward learning result on IPS. The method used was true experiment with pre-test post-test control group design. The population in the study are 4th grade student at SDN Sungguminasa II Somba Opu District Gowa Regency. Samples used are 40 student 20 student each from experiment and comparing group. chosen by simple random sampling. The data obtained from samples were analyzed with descritive and inferensial statistic. The result shows: 1) teacher ability in the implementation of cooperative learning Think Pair Share have increased, 2) student activities in the implementation of cooperative learning Think Pair Share, 3) student learning result who teached by cooperative learning Think Pair Share have increased, 4) student learning result who teached by lecture method have not increased, 5) the implementation of cooperative learning Think Pair Share is influencing toward learning result on IPS in 4th grade student at SDN Sungguminasa II Somba Opu District Gowa Regency.